N‐Doping of a Low‐Electron‐Affinity Polymer Used as an Electron‐Transport Layer in Organic Light‐Emitting Diodes. (27th February 2020) - Smith, Hannah L.; Dull, Jordan T.; Longhi, Elena; Barlow, Stephen; Rand, Barry P.; Marder, Seth R.; Kahn, Antoine
Abstract: n‐Doping electron‐transport layers (ETLs) increases their conductivity and improves electron injection into organic light‐emitting diodes (OLEDs). Because of the low electron affinity and large bandgaps of ETLs used in green and blue OLEDs, n‐doping has been notoriously more difficult for these materials. In this work, n‐doping of the polymer poly[(9, 9‐dioctylfluorene‐2, 7‐diyl)‐ alt ‐(benzo[2, 1, 3]thiadiazol‐4, 7‐diyl)] (F8BT) is demonstrated via solution processing, using the air‐stable n‐dopant (pentamethylcyclopentadienyl)(1, 3, 5‐trimethylbenzene)ruthenium dimer [RuCp*Mes]2 . Undoped and doped F8BT films are characterized using ultraviolet and inverse photoelectron spectroscopy. The ionization energy and electron affinity of the undoped F8BT are found to be 5.8 and 2.8 eV, respectively. Upon doping F8BT with [RuCp*Mes]2, the Fermi level shifts to within 0.25 eV of the F8BT lowest unoccupied molecular orbital, which is indicative of n‐doping. Conductivity measurements reveal a four orders of magnitude increase in the conductivity upon doping and irradiation with ultraviolet light. The [RuCp*Mes]2 ‐doped F8BT films are incorporated as an ETL into phosphorescent green OLEDs, and the luminance is improved by three orders of magnitude when compared to identical devices with an undoped F8BT ETL. Abstract : The n‐dopant [RuCp*Mes]2 is incorporated into the polymer F8BT via solution processing. Successful n‐doping is verified using photoelectron spectroscopy and conductivity measurements. The doped F8BT film is used as an electron‐transport layer in green organic light‐emitting diodes, allowing good electron injection and high luminance and external quantum efficiency.